Medallion depicting a kinnara with its tail forming a creeper motif - Temples of India Project Team (Jio Institute, 2024)
Tablet-like plaques are placed on the adhisthana (facing east). These plaques depict various types of flora and fauna as well as hybrid creatures like kinnara, vyala, and makara. The plaques are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The central artwork of the plaque is in the form of a circular medallion surrounded by a foliage motif. The medallion shows a kinnara (having the upper body of a human male and the lower body of a bird) with its tail forming a creeper motif. Kinnaras and kinnaris (having the upper body of a human female) are divine musicians who are skilled in dance, music, and poetry. The rest of the plaque surface is decorated with ardha padma (half lotus) and kalpa lata (creeper) motifs.